Breaking the DNA by soft X-rays in the water window reveals the scavenging and temporal behaviour of ·OH radicals - Vyšín, Luděk; Wachulak, Przemyslaw; Hájková, Věra; Davídková, Marie; Fiedorowicz, Henryk; Bartnik, Andrzej; Juha, Libor (Scientific reports, 2024)
A laser-plasma source emitting photons with energies in the water window spectral range has been used to reveal the radiation chemical yields of single-strand breaks in plasmid DNA as a function of ·OH radical scavenger concentration. Direct and indirect effects were investigated separately using DNA samples with various levels of hydration. We experimentally determined the value of the efficiency factor for strand cleavage in DNA caused by the reaction with ·OH radicals at 0.11, which was previously found in the theoretical studies. Additionally, the radiation chemical yield of ·OH radicals specific to the water window radiation emission of the source was determined by comparison with the gamma radiation-induced strand break yields. The ·OH radical yield determined using the plasmid DNA samples as a model was similar to the yield found using sensitive fluorescent dosimeters in previous experiments.
Keywords: Soft X-rays; OH radical; scavengery volných radikálů; DNA; voda; jednořetězcové zlomy DNA; Hydroxyl Radical; hydroxylový radikál; záření gama; Water; DNA Breaks, Single-Stranded; X-Rays; rentgenové záření; Gamma radiation; Free Radical Scavengers; Plasmids; plazmidy; Plasmid DNA; Radical scavengers; Gamma Rays